A Robust and Low-Complexity Gas Recognition Technique for On-Chip Tin-Oxide Gas Sensor Array. (8th July 2008) - Flitti, Farid; Far, Aicha; Guo, Bin; Bermak, Amine
Abstract : Gas recognition is a new emerging research area with many civil, military, and industrial applications. The success of any gas recognition system depends on its computational complexity and its robustness. In this work, we propose a new low-complexity recognition method which is tested and successfully validated for tin-oxide gas sensor array chip. The recognition system is based on a vector angle similarity measure between the query gas and the representatives of the different gas classes. The latter are obtained using a clustering algorithm based on the same measure within the training data set. Experimented results on our in-house gas sensors array show more than98 % of correct recognition. The robustness of the proposed method is tested by recognizing gas measurements with simulated drift. Less than1 % of performance degradation is noted at the worst case scenario which represents a significant improvement when compared to the current state-of-the-art.